First report of aflatoxin in dried yam chips in Benin - Bassa, S.; Mestres, C.; Champiat, D.; Hell, K.; Vernier, Philippe; Cardwell, K. (Scientific Societies, 2001)
Dried yam (Dioscorea spp.) chips are widely consumed in Bénin but are often attacked by molds. Invasion of food by Aspergillus flavus may lead to aflatoxin contamination. We report here the result of a survey on the sanitary quality of dried yam chips in Bénin. During July and August 2000, 50 dried yam chips samples were collected from different points in the marketing chain; 10 samples were collected from each of 5 stages: producers, wholesalers, retailers, dried yam-based food sellers and consumers. Aflatoxin content was assayed by the bio-luminescence method (1) after methanol/water extraction. Aflatoxins were detected in all dried yam chip samples, with levels ranging from 2.2 to 200 ppb and a mean value of 14 ppb. An aflatoxin concentration higher than the European Union's maximum residue limit (MRL) of 4 ppb was found in 98% of the samples (N = 50), while 6% had an aflatoxin concentration higher than the World Health Organization's MRL of 20 ppb. Molds were analyzed from two samples, each with aflatoxin levels around 5 ppb, on colony unit medium specific for A. flavus (2). Aspergillus spp. were detected in the inner part of dried yam chips of both samples, with a mean level of 9,000 CFU/g. Fusarium colonies were also present but were not identified to species.